Analisis Faktor Produksi dan Pendapatan Usahatani Padi Sistem Salibu di Desa Sabaran Kecamatan Jawai Selatan Kabupaten Sambas - Artiandi, Muhammad; Suyatno, Adi; Kurniati, Dewi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
Population growth that continues to increase, if not balanced by an increasing rice production, will lead to a shortage of rice supply in Indonesia. The "salibu" rice variety regrows after the remaining stems are cut, with shoots emerging from nodes within the soil. This study aims to determine the production factors and income of "salibu" rice farming. The respondents consisted of 50 rice farmers from Sabaran Village, South Jawai District, Sambas Regency. The analytical tool used was Cobb-Douglas production function regression analysis using SPSS 25 software. Based on the research results: 1) Land area significantly affects at a confidence level of α 0.01 or 1%, labor and NPK fertilizer significantly affect at a confidence level of α 0.05 or 5%, and urea fertilizer significantly affects at a confidence level of α 0.10 or 10%. However, insecticide, seeds, and growth regulators (ZPT) do not significantly affect production of "salibu" rice at α levels of 0.01, 0.05, and 0.10. 2) The income of "salibu" rice farmers is IDR 77,266,951/farmer/planting season. Meanwhile, when measured per harvest, the average income of farmers is sorted as IDR 22,740,690, IDR 28,579,835, and IDR 25,709,505.